Household Liquidity Constraints and Labor Market Outcomes: Evidence from a Danish Mortgage Reform - HE, ALEX XI; MAIRE, DANIEL LE (Journal of Finance, 2023)
ABSTRACT We study the causal effect of liquidity constraints on individual labor market outcomes by exploiting the 1992 mortgage reform in Denmark, which for the first time allowed homeowners to borrow against housing equity for nonhousing purposes. Following the reform, liquidity‐constrained homeowners increased debt levels and had higher earnings growth and lower employment rates. The option to borrow against housing equity enabled liquidity‐constrained individuals to move to high‐wage jobs and invest in valuable human and physical capital. The results imply that relaxing household liquidity constraints during recessions can create better job matches, potentially increasing earnings and output in the longer run.